Chemical Oxygen Demand (COD) and Total Suspended Solid (TSS) Removal from Rubber Wastewater Factory Using Electrocoagulation Technique - Munandar, Andika; Nabila, Khairratul; Azizah, Rifka Noor (Indonesian Journal of Environmental Management and Sustainability, 2023)
Rubber industrial wastewater is obtained during washing, shredding, grinding, crumbbing, drying, and pressing bokar. The wastewater produced can be an environmental pollutant because it contains relatively large amounts of organic matter. One alternative to treating rubber wastewater is to use the electrocoagulation process, which is a combination of the coagulation and electrolysis processes. This electrocoagulation process has several advantages in the form of simple equipment, short time, produces odorless wastewater, does not require large areas of land, and can remove various contaminants in water. In this study, rubber wastewater was treated by electrocoagulation using a batch system with variations in the contact time used, namely 20, 40, 60, 80, and 100 minutes. This type of research is experimental research, and descriptive analysis is carried out. Rubber wastewater is physically gray-black before treatment and chemically contains large organic matter. The results of this study showed that the content of chemical oxygen demand (COD) and total suspended solids (TSS) before processing had values of 691 mg/L and 317 mg/L. Optimum conditions for the elimination of COD and TSS contents were achieved within 80 minutes with the percentage of elimination being 89% and 85%.